Developing maneuver strategy for bowflag in liquid vaporizer industry - Adika Rangkuti, Dermovi; Toha, Mohamad (The Indonesian Journal of Business Administration, 2016)
Abstract - Personal vaporizer is a device that used to perform a similar activity as smoking but without the health hazard. One of the main elements in vaporizer is the liquid. Liquid on vaporizer is used to fill the vaporizer device with flavor so it can be consumed by their users. Bowflag liquid is one of the producers of liquid vaporizer who exist in the industry with fierce competition. Vaporizer industry is still new, young and small. The industry growth rate is high especially in the last couple of years. This growth comes with threats from outside the industry such as the possibility of strong cigarette companies entering the market or from inside of the industry itself including its market leaders and its new entrants emerging to the industry. To face the adversity, Bowflag require strategies to win the competition from cigarette industry and liquid industry. Therefore research is needed to determine what strategy maneuver Bowflag should conducted to face this adversity. To formulate the required strategies a serial steps of attack strategy formulation was conducted. These steps are external and internal environment scanning, customers perception study, maneuver strategy to face cigarette formulation and maneuver strategy to win in the liquid industry. The required data and information for this study captured using both qualitative and quantitative with interview and survey. The findings from this research are supportive external-internal environment, bypass strategy maneuver usage to face cigarette competitor and frontal maneuver usage to compete with other liquid companies. Bowflag must create entry barrier while stealing the market from cigarette companies and perform head to head combat to other liquid companies in the industry, with quality as its main weapon. Bowflag must conduct the strategy integration and develop business model.Keywords: strategy moves, maneuver strategy, attack strategy, Bowflag, business model, target market, entry barrier.